Mapping the Scientific Outputs in the Field of Physiotherapy: A Co-Word Analysis - Emami, Zahra; Joulahi, Laleh; Okhovatian , Farshad; Shahrokhifarid , Razieh (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Evaluation and analysis of scientific outputs and between-keywords relationship could provide the investigators with useful information. The aim of this study was mapping of scientific outputs in the field of physiotherapy, with applying the co-word analysis in the ISI Web of Science database. Methods and Materials: This study was a scientometric approach using the co-word and network analyses in the field of physiotherapy. Published papers from 2000 to 2018 were reviewed and the results were analyzed by Excel, UCINET, Netdraw and VOSviewer. Results: Results showed an increasing trend of scientific outputs in the field of physiotherapy. United States of America (USA) achieved the first rank (7400 documents) followed by England and Australia. Among the Middle East countries, Turkish with 981 documents achieved the first rank while Iran with 235 documents owned the third rank. Regarding the frequently used subjects, the most scientific outputs in the field of physiotherapy were shared with Physical medicine and Rehabilitation, Orthopedic, Neuroscience, Sport medicine, Internal medicine, Surgery, Rheumatology, Health medicine, Pediatrics, and Pulmonology. Results revealed rehabilitation, physiotherapy, exercise, physical therapy, and management based on degree centrality and disability, therapy, physiotherapy, outcome based on both of the betweenness and closeness centrality had the most impact on the network. Conclusion: Regarding the trend of scientific outputs, physiotherapy is most related to orthopedic, neuroscience, and pediatric. Moreover, scientific interaction to increase scientific outputs in Iran and other Middle East countries seems to be essential. Additionally, mapping of co-word analyses could provide the policy makers with information regarding the research, key words, and the relationship between key words in the field of physiotherapy. Therefore, they can plan essential and appropriate programs to improve both the quality and quantity of the scientific outputs in this field.